2021
DOI: 10.1002/ece3.7824
|View full text |Cite
|
Sign up to set email alerts
|

Functional assembly of tropical montane tree islands in the Atlantic Forest is shaped by stress tolerance, bamboo presence, and facilitation

Abstract: Aims: Amidst the Campos de Altitude (Highland Grasslands) in the Brazilian Atlantic Forest, woody communities grow either clustered in tree islands or interspersed within the herbaceous matrix. The functional ecology, diversity, and biotic processes shaping these plant communities are largely unstudied. We characterized the functional assembly and diversity of these tropical montane woody communities and investigated how they fit within Grime's CSR (C-competitor, S-stress-tolerant, Rruderal) scheme, what funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(107 reference statements)
1
2
0
Order By: Relevance
“…The species pool of Pedra do Pato consisted mainly of pure stress-tolerant species, which was expected because of the harsh conditions found in high elevation areas, such as the poor soil, high radiation, strong wind, and colder temperatures . Additionally, the competitive dimension had a great contribution to the strategy spectrum found, as observed for other campos de altitude and Páramos sites (Christmann et al 2021, Cruz and Lasso 2021. The presence of so many competitive and competitive/stress-tolerant species might be related to the high precipitation during the rainy season and the presence of fog all over the year (Safford 1999, Assis and, and it is an indicator of more productivity in comparison with the high elevation formations of central Brazil, like the campos rupestres, composed primarily of more stress-tolerant species .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The species pool of Pedra do Pato consisted mainly of pure stress-tolerant species, which was expected because of the harsh conditions found in high elevation areas, such as the poor soil, high radiation, strong wind, and colder temperatures . Additionally, the competitive dimension had a great contribution to the strategy spectrum found, as observed for other campos de altitude and Páramos sites (Christmann et al 2021, Cruz and Lasso 2021. The presence of so many competitive and competitive/stress-tolerant species might be related to the high precipitation during the rainy season and the presence of fog all over the year (Safford 1999, Assis and, and it is an indicator of more productivity in comparison with the high elevation formations of central Brazil, like the campos rupestres, composed primarily of more stress-tolerant species .…”
Section: Discussionsupporting
confidence: 61%
“…In this case, competition results in convergence for specific traits similarly to what is expected for abiotic filtering(Grime 2006, Mayfield and. In the Brazilian Páramos, for example, the presence of a bamboo species with resprouting ability after fire is associated with low functional diversity in tree islands, where it dominates after wildfires(Safford 2001, Christmann et al 2021.Nonetheless, if no set of traits allows better competitive ability, species are expected to diverge in niches to avoid competition for resources(MacArthur and Levins 1967, Scherrer et al 2019.Pastore et al (…”
mentioning
confidence: 99%
“…Mongolian Oak broadleaves and P. koraiensis needles were ignited 72 and 39 times, respectively, with corresponding ignition probabilities of 3.33% and 1.81% [18]. The fuelbed of P. massoniana is more difficult to ignite than the broadleaf bed of Mongolian Oak because of the differing leaf shapes of the broadleaves and conifers [36,37]. Through repeated cigarette butt-throwing experiments, it was found that cigarette butts tended to first smolder, gradually carbonize the litter, and finally transform that smolder into an open flame with the action of wind [38].…”
Section: Number Of Ignitionmentioning
confidence: 99%